Intertemporal trends in agricultural productivity - Benin, Samuel; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2016)
Changes or trends in agricultural productivity over time can shed light on the relative sources of agricultural growth as well as on resource and factor constraints to increasing agricultural production sustainably. Because improvements in agricultural productivity are important for reducing poverty and achieving other development objectives, it is essential to use the appropriate indicator and measure of agricultural productivity— partial factor productivity (PFP) or total factor productivity (TFP). However, because productivity embodies many different components, changes in productivity can catalyze a wide range of direct and indirect effects on the pathways to achieving different development objectives.